An Overview on Resources for Development of Hindi Speech Synthesis System - Balyan, Archana (New Ideas Concerning Science and Technology Vol. 11, 2021)
Most of the information in digital world is accessible to few who can read or understand a particular language. The speech corpus acquisition is an essential part of all spoken technology systems. The quality and the volume of speech data in corpus directly affect the accuracy of the system. However, there are a lot of scopes to develop speech technology system using Hindi language which is spoken primarily in India. To achieve such an ambitious goal, the collection of standard database is a prerequisite. This paper summarizes the Hindi corpus and lexical resources being developed by various organizations across the country. In this paper, a survey of efforts in database developments for Hindi language has been performed. It discusses some core linguistic resources of Hindi language, available through various resources developed for usage in text-to-speech synthesis and speech recognition technology.